Modelo de Gestión para la Unidad de Turismo del Cantón Penipe Provinci de Chimborazo. - Mariño Olivo, Fernanda Cristina (2014)
Tourism is still expanding globally, favoring areas, countries and potential destinations, developing careful planning strategies that respond to the new demands and the need for sustainable and operational management. The Management Model for the tourism unit in the Penipe canton, Chimborazo province will be a tool that will allow economic and tourist development for valuing the natural and cultural resources of the canton. After an analysis of the potentialities that our country and the province of Chimborazo have, and with the growing trend of tourist activities, there is an increase of 11,47% of tourists visiting our country taking reference from the year 2011 with 1’141.037 tourists and 2012 with 1’271.953, from which 104.156 tourists entered the province of Chimborazo and the Penipe canton because of El Altar snowcapped mountain with 538 tourists, the situational analysis of the canton was developed resulting that the infrastructure mentioned is suitable for tourism development. The research was conducted by taking into account the number of tourists who entered El Altar snowcapped mountain and the economically active population, the starting base was the inventory of the attractions in the canton through field visits and verification of the existing data, after the implementation of the survey, the data were tabulated in order to obtain the profile of tourists.